Development of blue-light GaN based micro light-emitting diodes using ion implantation technology - Yu-Hsuan Hsu; Shao-Hua Lin; Dong-Sing Wuu; Ray-Hua Horng (Discover Nano)
Abstract This study fabricated 10 μm chip size μLEDs of blue-light GaN based epilayers structure with different mesa processes using dry etching and ion implantation technology. Two ion sources, As and Ar, were applied to implant into the LED structure to achieve material isolation and avoid defects on the mesa sidewall caused by the plasma process. Excellent turn-on behavior was obtained in both ion-implanted samples, which also exhibited lower leakage current compared to the sample fabricated by the dry etching process. Additionally, lower dynamic resistance (Rd) and series resistance (Rs) were obtained with Ar implantation, leading to a better wall-plug efficiency of 10.66% in this sample. Consequently, outstanding external quantum efficiency (EQE) values were also present in both implant samples, particularly in the sample implanted with Ar ions. This study proves that reducing defects on the mesa sidewall can further enhance device properties by suppressing non-radiative recombination behavior in small chip size devices. Overall, if implantation is used to replace the traditional dry etching process for mesa fabrication, the ideality factor can decrease from 11.89 to 2.2, and EQE can improve from 8.67 to 11.03%.